(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
this study analyzes the scientific basis of mechanical and aerodynamic approaches aimed at increasing the efficiency of separating raw cotton from large and small trash. It was established that in the traditional BCH-2M, CHX-3M2, CHX-5, and APT-12 cleaners, due to insufficient optimization of impact energy, inertial differentiation, grate geometry, and loosening dynamics, there is a technological imbalance between cleaning efficiency and fiber damage. In the study, a design model of a new generation UXK unit was developed that eliminates this problem; it combines multi-stage mechanical selection, an optimized grate profile, the impact-displacement mechanism of the saw drum-grate pair, and aerodynamic separation zones. Experimental analysis shows that the cleaning efficiency of the UXK machine has increased, cotton losses have decreased, and fiber damage has significantly decreased. The research results propose constructive solutions for achieving high quality, energy efficiency, and technological stability in the cotton ginning industry